Rescue Surgery 19 Years after Composite Root and Hemiarch Replacement. (10th April 2013) - von Aspern, Konstantin; Seeburger, Joerg; Etz, Christian D.; Sauer, Matthias; Lehmkuhl, Lukas; Misfeld, Martin; Mohr, Friedrich W.
Abstract : A 59-year-old male patient with Marfan's syndrome was referred to our clinic due to acute chest pain. His medical history contains complex surgery for type A aortic dissection 19 years ago including composite root replacement using a mechanical aortic valve. Immediate computed tomography indicated perforation at the distal ascending aortic anastomosis plus complete avulsion of both coronary ostia. The patient underwent successful rescue surgery with ascending aortic and arch replacement using a modified Cabrol technique.